Effect of Arthrospira Platensis (Spirulina) and Azolla Pinnata on Growth Performance and Hematology of the Freshwater Fish Oreochromis Mossambicus (Tilapia): Life Sciences-Aquaculture - Sakthivel, M; Sahaya Leon, J.Prakash (International Journal of Life Science and Pharma Research, 2022)
Aquaculture is identified as the viable alternative source, for increasing fish production to meet out ever growing demand for fish consumption. Due to their high nutritive value, toxic-free, environment friendly and high productivity Azolla and Spirulina were considered as promising feed. The knowledge of hematological and growth characteristics is an important tool that can be used as a sensitive and effective index to monitor pathological and physiological changes in fish. Consumption of Azolla and Spirulina by fish can have direct or indirect effects on human health. In the present study, a survey was conducted in humans to analyze the effect of Azolla, Spirulina through fish tilapia consumption and also to analyze the hematological and growth changes the fish Oreochromis mossambicus were exposed to different concentrations of spirulina and Azolla with commercial fish feed. Fishes were selected for the weight of (21gram) and length of (11cm) for the present experiment. In the control group, 6 fishes were exposed to 20 grams of commercial fish feed. In the first group T1 (experiment 1) 6 fishes were exposed to 8 grams of Azolla with 12 grams of commercial fish feed, in the second group T2 (experiment 2) 6 fishes were exposed 8 grams of Spirulina with 12 gram of commercial fish feed and in the third group T3 (experiment3) 6 fishes were exposed 4 grams of Azolla and 4 grams of Spirulina with 12 gram of commercial fish feed for 60 days. In the present investigation, growth level was increased when fish Oreochromis mossambicus was exposed to different concentrations of Spirulina and Azolla with commercial fish feed, and also significant differences were observed in the blood parameters like white blood cells (WBC), Red blood cells (RBC), Hemoglobin (HB), MCV and MCH. A questionnaire-based dietary survey of tilapia consumers were collected in detail through face-to-face interviews at fish shops located nearby KRP Dam, Krishnagiri district. Statistical data were analyzed using SPSS software and all tests were considered significant at p<0:05. Main objective of the present study is to analyze the growth and hematological effect of Azolla, Spirulina in fish tilapia and also to identify the fish (Oreochromis mossambicus) consuming people through questionnaire-based survey. It is concluded that more people consumed fish tilapia as a common food and fish fed with azola and spirulina showed rich nutritive value. So, the present study recommended that, if the fish tilapia is fed with azolla and spirulina, this may increase the nutritive states of human populations via fish Tilapia.